Mental Health Literacy in Adolescents: From recognition to looking for help. Systematic Review of Literature - Rosa, Amorim Gabriel Santos (2013)
Background: Mental disorders often arise in adolescence and have a deep impact on adolescents and families. However, in the most frequent situations, adolescents do not receive appropriate help, while for the more severe psychotic disorders, help is received with much delay. The low level of Mental Health Literacy is crucial to the lack of help-seeking behaviors during adolescence, affecting the development and increasing the risk of recurrence of the disorders. Aim: This review aims to systematize the current knowledge on Mental Health Literacy in adolescents, focusing on the recognition of the disorder and help seeking behavior for the most common mental health problems: depression; anxiety and emotional stress, and substance abuse. Methods: Eleven published studies of recognition of mental disorders and help-seeking in adolescents were identified through searches of CINAHL, Medline, B-on and RCAAP. A thematic analysis was undertaken on the results reported in the quantitative and qualitative literature. Results: Adolescents showed difficulties in the recognition and identification of the key symptoms of mental disorders. Levels of recognition are higher in depression, especially in the presence of severe symptoms. Stigma, resilience and preference for informal help are the main barriers to accessing professional help. Insecurity and lack of confidence on individual capacities conditioned the first aid. Conclusions: New technologies (e.g. Internet and SMS) and school programs are important sources of support and promotion of mental health literacy. Strategies for improving recognition and help-seeking by adolescents should focus on improving mental health literacy, reducing stigma, and taking into account the desire of adolescents for resilience and self-reliance.